Autobiographisches Schreiben in Alfred Anderschs Prosa der 50er Jahre - Jabłkowska, Joanna (Studia Germanica Posnaniensia, 2017)
Alfred Andersch´s autobiographical texts from the 1950s have been heavily criticized in recent literature on the topic. W.G. Sebald´s essay about Andersch was of crucial importance. The details of Andersch´s stay in the Dachau concentration camp as well as the writer´s motivation to desert at the end of the war were questioned. The article aims at a new reading of Andersch´s autobiographical texts with regard to their credibility. It compares the early short story Flucht in Eturien with the autobiography Die Kirschen der Freiheit and a few less known texts. The analysis leads to the conclusion that Andersch “re-wrote” his biography as a creation that fulfils unconscious wishes of a whole generation. His intention was to adapt the image of decent young men of antifascist beliefs whose only guilt was the loyalty to their comrades.